Enhanced sustainable methane production from anaerobic co-digestion of POME using UASBR (pH effects) - Wong, Jung Weng (2018)
Malaysia is one of the biggest country that producer and exporter of the palm oil. Palm oil mills is used to process and generate palm oil from it fruit bunch. Large quantities of water are used during the extraction of crude palm oil from the fresh fruit bunch, and about 50% of the water results in palm oil mill effluent (POME). POME without proper treatment and left in the pond will decompose and generate methane gas which is a gas that can cause greenhouse effect. Methane gas is a harmful gas that 20 times stronger than Carbon dioxide in greenhouse effect if it attaches to the atmosphere. In order to prevent it happen to our environment, an enclose treatment method anaerobic co-digestion (ACD) by using upflow anaerobic sludge blanket reactor (UASBR) is used to treat POME as the microorganism in the sludge blanket digest the waste want organic passing through it. Anaerobic co-digestion can improve the methane production in mixing different type of material together. In this study, POME and cow manure is selected as our substrates in ratio of 50:50. During the digestion, the generated gas is collected and can be used for other purpose. In this paper, the different pH on affecting the methane production is study. The different pH (6.5, 7.0, 7.5) is used to observe the methane gas can be better generate in which pH. At the end of the study, the results showed that pH 7.0 give better methane production (76.7%) out of the total gas produced compared to the pH 6.5 (68.4%) and also pH 7.5 (60.6%), this is because the microorganism was pro-active and won’t be affected by acidic or alkali base in degrading the organic, and hence, produce highest methane gas. This shows that the waste organic is more friendly to degrade in the pH 7.0 in order for it to digest and produce high amount of methane gas.